The Theoretical Foundations of Regulation on Public Finances - Nagy, Zoltán (Regulation of Public Finances in Light of Financial Constitutionality: Analysis on Certain Central and Eastern European Countries, 2022)
Financial policy—which is based on macroeconomic policy—can be divided into two parts: fiscal (budgetary) policy, and monetary policy. Fiscal policy essentially covers the area of public revenues and public expenditures, i.e., it deals with public burdens through the obligation of burden-sharing, taxation, and public expenditures, from which public services are financed. The fiscal policy of the modern state is a complex and difficult system in which the individual elements are closely related to each other. Budgetary policy manifests in the regulation of public finances and public charges (taxes). Monetary policy is the other element of financial policy that primarily regulates financial processes indirectly. An important task of the monetary sphere is to ensure the money supply and smooth cash flow of the economy, i.e., to have enough money available for economic processes. Besides the central bank, financial intermediaries participate in the processes at micro level, the regulation of which is also one of the tasks of the central bank as well as the state. The two branches of monetary policy are closely related with each other. They are defined by different sub-goals, but the main goal of fiscal policy is to ensure economic and social stability and development. The regulation of public finances has two tasks: to regulate the public finance system and related issues, and to regulate the monetary system itself. To make the regulation of the financial system comprehensible, it is necessary to learn about the role and function of the state in public finances, the essential characteristics of money, and the principles of the functioning of the monetary system. This theoretical chapter deals analyses these issues. KEYWORDS: Public services, public finances, fiscal policy, monetary policy, financial system.